2021
DOI: 10.1177/13524585211001781
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and multiple sclerosis: A Mendelian randomization study

Abstract: Background: Higher childhood body mass index (BMI) has been associated with an increased risk of multiple sclerosis (MS). Objective: To evaluate whether childhood BMI has a causal influence on MS, and whether this putative effect is independent from early adult obesity and pubertal timing. Methods: We performed Mendelian randomization (MR) using summary genetic data on 14,802 MS cases and 26,703 controls. Large-scale genome-wide association studies provided estimates for BMI in childhood ( n = 47,541) and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…One of the most recent research studies on the topic is the Mendelian randomization study conducted by (Harroud et al, 2021). Including large cohorts of MS and control cases, authors showed that higher childhood BMI is associated with agreater risk of MS, independent of age at puberty [ 14 ]. Thus, besides environmental factors, genetic evidence also confirms the influence of childhood obesity on MS susceptibility.…”
Section: Obesity As An Environmental Risk Factor In Multiple Sclerosismentioning
confidence: 99%
“…One of the most recent research studies on the topic is the Mendelian randomization study conducted by (Harroud et al, 2021). Including large cohorts of MS and control cases, authors showed that higher childhood BMI is associated with agreater risk of MS, independent of age at puberty [ 14 ]. Thus, besides environmental factors, genetic evidence also confirms the influence of childhood obesity on MS susceptibility.…”
Section: Obesity As An Environmental Risk Factor In Multiple Sclerosismentioning
confidence: 99%
“…Observational data supports the concept that BMI during adolescence, particularly late teenage years, is a risk factor for MS 4,7,9,18 . Mendelian randomisation studies have strengthened the notion that this may be a causal relationship 5,6 . It remains debatable whether childhood BMI is a causal risk factor for MS independently of its persistence into adolescence/adulthood, or whether it purely affects MS risk via its strong correlation with BMI in early adult life.…”
Section: Discussionmentioning
confidence: 99%
“…It remains debatable whether childhood BMI is a causal risk factor for MS independently of its persistence into adolescence/adulthood, or whether it purely affects MS risk via its strong correlation with BMI in early adult life. In favour of the latter, a recent study used multivariable MR to regress out the effects of genetic instruments for childhood BMI mediated via adult BMI: controlling for the effect of adult BMI abolished the observed MR effect of childhood BMI on MS risk, suggesting that persistently raised BMI into adulthood, rather than transiently increased BMI during childhood, is the causal risk factor 6 . These results, obtained with larger datasets for early life BMI, suggest that what we observe may be driven by the same phenomenon - pleiotropic SNPs acting on MS risk via their effect on BMI in later life rather than in childhood per se .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing world-wide obesity epidemic has multiple deleterious effects on public health and has also been associated with an increased risk of MS [46]. Increased obesity leads to lower levels of 25-hydroxyvitamin D which in turn predisposes to MS [47]. The association between obesity and MS is similar among men and women, and the observed trend of higher BMI resulted in a higher risk of developing MS [48].…”
Section: Discussionmentioning
confidence: 99%